Voz e educação em saúde: validação de conteúdo de um curso oferecido remotamente para professores universitários - Ferraz, Pablo Rodrigo Rocha (2021)
Introduction: over the years, the vocal complaints and symptoms are added to the important influence that the work has on the teacher's health. Specifically, the Higher Education sector in its process of restructuring and adaptation to the new socioeconomic scenario and the production of science, technology and innovation, generates new demands that imply transformations in the organization of the work of this professional. Thus, the elaboration of intervention proposals that encourage changes in habits and the promotion of strategies for environmental adjustments and work organization are fundamental. Objective: to elaborate and to validate as to form and content an action proposal for university professors regarding the issues of voice care. Method: the research was divided into two studies. In Study 1, the objective was to elaborate and describe the structure of the course "Teacher: let's take care of your voice?" to be offered in the distance modality and in asynchronous communication. The course was organized under two axes: the form (considering the number of modules, workload, reflection questions before and after each module, among others) and the content (considering the physiological/functional aspects of the voice, posture, expressiveness, emotion, voice characteristics related to work and teaching in higher education). In Study 2, the objective was to validate the form and content of the course "Teacher: let's take care of your voice?" by teacher judges with experience in distance education (DE) and speech therapist judges with experience in voice issues, especially with teachers. They participated in the validation process carried out by means of a Focus Group and considered aspects related to the form, content and instruments of Course Evaluation. The judges' participation was videotaped and transcribed, and the material was submitted to content analysis, when categories were defined. Results: Regarding the course evaluation, for the form parameter, the items "script", "layout", "schedule appropriate to the workload" and "interaction/tutoring/forum" were the items that had comments with suggestions for changes, while for the content parameter the items "content x context" and "content/learning evaluation". As for the evaluation of the Course Evaluation instruments, the judges suggested changing the terms "Insufficient" and "Sufficient" on the answer scale to "Poor" and "Very good", respectively; changing the term "How much" at the beginning of the questions to "How"; and changing the values on the answer scale from "0 to 10" to "0 to 100" for the instruments called Voice Knowledge Research, to be presented before and after the teachers have completed the course. At the end, the course and the evaluation instruments were re-designed considering the suggestions given. Conclusion: The studies developed for this thesis, after the validation stage of the form and content of the course and of the evaluation instruments, showed that the course offered in the DE modality reaches the objective, which is to sensitize the university professor, as to issues related to voice care, and may be submitted to final validation, when it will be presented to college professors